2016
DOI: 10.1111/tmi.12725
|View full text |Cite
|
Sign up to set email alerts
|

Child diarrhoea and nutritional status in rural Rwanda: a cross‐sectional study to explore contributing environmental and demographic factors

Abstract: Abstractobjective To explore associations of environmental and demographic factors with diarrhoea and nutritional status among children in Rusizi district, Rwanda.methods We obtained cross-sectional data from 8847 households in May-August 2013 from a baseline survey conducted for an evaluation of an integrated health intervention. We collected data on diarrhoea, water quality, and environmental and demographic factors from households with children <5, and anthropometry from children <2. We conducted log-binomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
(45 reference statements)
1
22
1
1
Order By: Relevance
“…However, water quality was not associated with z-score for HAZ and WAZ which indicates its effect being either neutralized for more severe forms of undernutrition or children experiencing catch-up growth with no major impact on long term nutritional health in a Nepalese context. Nevertheless, other studies have reported significant associations between water treatment practices and childhood stunting [35,44]. The discrepancies in study findings could be due to various reasons such as cultural factors that determine water handling practices [45] and effectiveness of household water purification techniques [46] that determines the quality of water and thus leading to a varying effect on nutritional outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…However, water quality was not associated with z-score for HAZ and WAZ which indicates its effect being either neutralized for more severe forms of undernutrition or children experiencing catch-up growth with no major impact on long term nutritional health in a Nepalese context. Nevertheless, other studies have reported significant associations between water treatment practices and childhood stunting [35,44]. The discrepancies in study findings could be due to various reasons such as cultural factors that determine water handling practices [45] and effectiveness of household water purification techniques [46] that determines the quality of water and thus leading to a varying effect on nutritional outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…We did a baseline survey of the 150 villages, which included water sampling. 8 To increase the study's power to accurately detect improvements in child health, we stratified the 150 villages along two dimensions: average fraction of children younger than 2 years with caregiver-reported diarrhoea in the previous 7 days; and average wealth index, which is a standardised variable (mean 0·04 [SD 0·67]). The wealth index is a weighted average of a household's ownership of 17 assets in three categories: durable goods such as refrigerator, television, and bicycle; large livestock such as cattle, goats, or sheep; and attributes of the housing structure, such as the roofing, wall, and floor materials.…”
Section: Methodsmentioning
confidence: 99%
“…Diarrheal disease is a leading cause of morbidity and mortality in Rwanda, 1,2 and environmental and demographic factors contribute to both diarrhea and stunting in the country. 8 Household water treatment (HWT) appears to be effective in reducing diarrheal disease among populations with unsafe sources of drinking water. 9 Evidence of its effectiveness, however, is derived from nonblinded trials that report diarrheal disease as an outcome.…”
Section: Introductionmentioning
confidence: 99%